Occupational safety & health management system practical guide for implementation - Aziz Basiran; Mohd. Rafee Baharudin; Fakhrul Anwar (McGraw-Hill Education (Malaysia) Sdn Bhd., 2016)
This book is an all-inclusive book covering the fundamental principles of OSHMS for certification